Methodological model of the budget process of the European Union - S.V. Svirko; V.V. Dovhalyuk; T.M. Trosteniuk (Економіка, управління та адміністрування)
European integration processes in Ukraine have gained final activation, which requires the fastest solution to the entire set of tasks set by the European Union for Ukraine. In the context of the formation of an effective, efficient and effective national system of public finance management, the study of all components of the public finances of the European Union, in particular the budget of the last economic and political union, is of particular importance. On the basis of the development of a wide range of regulatory documents that make up the budget legislation of the European Union, the definition of the budget process of the European Union has been singled out and developed (by which it is proposed to understand the process of formation (forecasting, planning , processing, approval), implementation (implementation of planned budget transactions within the general management of budget allocations, their accounting, including financial and budget reporting, control and audit, assessment, monitoring) of the budget indicators of the European Union, presented in the multi-year financial program and budget the EU), its mission (which is seen as ensuring the uninterrupted functioning of the institutions of the general public administration sector for further economic, social, political, scientific and technical, ecological and other types of social development of the EU), budgetary principles (general and special), functions, stages, tools and methods, on the basis of which a methodological model of the budget process of the European Union was formed, which has a clear system-forming framework and substantiated substantive positions for each of the methodological clusters. Its final implementation and further implementation into the domestic practice of the budget process will allow not only to increase the efficiency and effectiveness of the budget cycle of the European Union, and therefore, as a result, will contribute to a better performance of the latter’s mission and function, but will also ensure the maximum approximation of the domestic process to European guidelines in the conditions forcing European integration processes in Ukraine.